Badania marketingowe w polskich małych i średnich przedsiębiorstwach w kontekście ich obecności w Unii Europejskiej - Oczachowski, Dariusz (Marketing Research in Polish Small and Medium Size Enterprises in the Context of Their Presence in the European Union, 2006)
The situation of Polish small and medium-size enterprises operating on highly competitive European markets differ from that of bigger ones in relation to the ways of gaining and applying marketing knowledge. Small enterprises possess more modest resources and have to match expensive information needs which continuously grow. Such circumstances put these enterprises in a difficult situation, because on the one hand they cannot afford to hire professional marketing research institutions, on the other - they cannot perform necessary research procedure themselves for the lack of satisfactory potential. A solution to this dilemma may prove the acceptance by small enterprises the research-oriented culture which distinctive feature would be employing people who could be used for increasing firm's knowledge about itself and the market. They must understand the idea of learning society and willing to self-develop. The managers' task is to make their employees' continuously growing knowledge useful for the whole organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 187-193